(Re-)producing bioassemblages: positionalities of regional bioeconomy development in Finland. Issue 4 (3rd April 2019) - Albrecht, Moritz
ABSTRACT: Bioeconomy is a new political and economic buzzword that frames many proposed pathways to sustainable regional development in Europe, particularly in rural, biomass rich areas. Dissected by research into various strands, visions, shades of "green" and presented by bioeconomy stakeholders through regional examples and self-promoting bio-clusters, the socio-spatial processes of regional assemblages are often ignored in these accounts. Based on a prominent Finnish example, this case study employs the concept of bioassemblage to display the socio-spatial positionalities of regional bioeconomy development in the places of materialisation. Furthermore, it ties the spatial (re-)production of bioassemblages to their role as bioeconomy policy translation loops and consequently provides insights into the processes of bioeconomy policy mobility, translation and mutation. Examining the positionalities in a bioassemblage presents a complex and frequently shifting local environment accompanied by unequal power topologies and means of territorialisation. Shallow policy narratives create problematic mismatches between the "best-practices" employed by policy makers and regional bioeconomy materialisation in the places themselves. While the study makes no assumption on the sustained future of bioeconomy development, it shows that current processes enable the externalisation of risks at industrial sites, restrict wider participation and discredit the important role of institutional actors in development.